2008
DOI: 10.1002/jmri.21539
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral blood perfusion reduction associated with vertebral bone mineral density reduction: A dynamic contrast‐enhanced MRI study in a rat orchiectomy model

Abstract: Purpose: To investigate the relationship between vertebral blood perfusion and vertebral bone mineral density (BMD) in a rat orchiectomy (ORX) model. Materials and Methods:Nine 6-month-old male WistarKyoto rats were used. Computed tomography (CT) bone densitometry and dynamic MRI were performed at baseline and four weeks post-ORX. MRI was performed on a 1.5T clinical MR scanner with a small surface coil placed under the rat lumbar spine region. A sagittal midsection of the lumbar spine was prescribed. Dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…According to laboratory research reported so far, osteoporosis after orchiectomy occurs via three mechanisms: 1) a decrease in calcium reabsorption and an imbalance in bone metabolism following sex hormone deprivation can lead to lowered BMD, 2) an increase in receptor activators of nuclear factor kappa-B ligand (RANKL) in bone marrow (which upregulates free soluble RANKL in the bone marrow of aged rats) can stimulate bone metabolism,22 particularly increased bone turnover in association with increased serum ALP and osteocalcin levels, 2324 and 3) loss of spinal BMD after orchiectomy is correlated with a decrease in spinal blood flow 25…”
Section: Discussionmentioning
confidence: 99%
“…According to laboratory research reported so far, osteoporosis after orchiectomy occurs via three mechanisms: 1) a decrease in calcium reabsorption and an imbalance in bone metabolism following sex hormone deprivation can lead to lowered BMD, 2) an increase in receptor activators of nuclear factor kappa-B ligand (RANKL) in bone marrow (which upregulates free soluble RANKL in the bone marrow of aged rats) can stimulate bone metabolism,22 particularly increased bone turnover in association with increased serum ALP and osteocalcin levels, 2324 and 3) loss of spinal BMD after orchiectomy is correlated with a decrease in spinal blood flow 25…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the relationship between BMD and bone perfusion, several authors have reported that MRI-derived perfusion parameters of vertebral bone marrow were decreased significantly in osteoporotic subjects compared with those of normal subjects [17][18][19][20][21][22]. These results suggest that a decrease in vertebral blood flow may be associated with a decrease in the BMD.…”
Section: Introductionmentioning
confidence: 54%
“…Bone demineralization depends on various factors, such as bone perfusion, metabolism of bone cells, and the structure of the bone matrix [19]. Thus, being able to predict these factors noninvasively before significant bone loss occurs would help to prevent BMD decline in postmenopausal women and, consequently, to lower their incidence of compression fractures [7].…”
Section: Discussionmentioning
confidence: 99%
“…Osteotomy of the proximal femur reduces intra-osseous pressure and pain in patients with osteoarthritis of the hip [14]. MR signal changes observed via DCE MRI can be due to a combination of, among other things, capillary permeability, tissue blood perfusion and interstitial tissue pressure [11,[16][17][18]. In the DCE MRI study, washout is related to the back-flow of contrast agent from interstitial space to the bloodstream and the elimination of contrast agent from the body via the kidneys.…”
Section: Discussionmentioning
confidence: 99%